1979
DOI: 10.1042/bj1800095
|View full text |Cite
|
Sign up to set email alerts
|

Total, latent and active collagenase during the course of post-partum involution of the rat uterus. Effect of oestradiol

Abstract: 1. Total, active and latent collagenase activities were determined by direct assay of tissue homogenates. 2. The rate of collagen breakdown during post-partum involution of the rat uterus is correlated with the total activity of collagenase. Both are low at parturition, reach a maximum within 24h and fall slowly to low values of 5 days post partum. This temporal correlation strongly supports the hypothesis that collagenase participates in collagen breakdown in vivo. 3. Further support for this hypothesis is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 23 publications
4
32
1
1
Order By: Relevance
“…This result agrees with biochemical studies (Jeffrey et al, 1971;Halme and Woessner, 1975). On the day of parturition, there is little collagenase, the majority being procollagenase that is not yet activated (Woessner, 1979;Roswit et al, 1983). The principal cellular origin of procollagenase is obscure.…”
Section: Discussionsupporting
confidence: 93%
“…This result agrees with biochemical studies (Jeffrey et al, 1971;Halme and Woessner, 1975). On the day of parturition, there is little collagenase, the majority being procollagenase that is not yet activated (Woessner, 1979;Roswit et al, 1983). The principal cellular origin of procollagenase is obscure.…”
Section: Discussionsupporting
confidence: 93%
“…Ryan & Woessner (1972) showed that administration of E 2 to parturient rats strongly inhibits the loss of collagen from the involuting uterus, and found that this effect is due to inhibition of collagen degradation rather than stimulation of collagen synthesis. Furthermore, Woessner (1979) found that injection with E 2 causes a decrease in uterine collagenase activity that is correlated with the rate of collagen breakdown. Frankel et al (1988) found that E 2 induces alpha 2 (I) and alpha 1 (III) collagen mRNAs in the immature rat uterus, and Dyer et al (1980) reported that E 2 stimulates both synthesis and degradation of collagen in the ovariectomized rat uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the postpartum collagen degradation might occur in the edematous area at PM. However, the majority of eollagenase is latent at PM [Woessner, 1979;Rosvvit et al. 19831.…”
Section: Discussionmentioning
confidence: 99%
“…19831. Telopeptidase, which can cleave the C-terminal cross-linkage for stabilizing collagen fibers, exists in the postpartum uterus [Nakano and Scott, 1987], In contrast to eollagenase which does not reach a maximal activity until postpartum day 1 [Woessner. 1979], telopeptidase activity shows a maximum immediately after parturition [Nakano and Scott.…”
Section: Discussionmentioning
confidence: 99%